Effect of marsupialization on the healing of fistulotomy wounds of simple anal fistula: a randomized control trial - Raslan, Mohamed M. (International Surgery Journal, 2018)
Background: An anal fistula is traditionally treated by fistulotomy, adding marsupialization of fistulotomy wounds is optional. The aim of the current study was to compare the outcomes of fistulotomy with marsupialization and fistulotomy alone for simple anal fistula on healing rates and post-operative complications Methods: 50 patients with simple anal fistula randomly allocated to two groups fistulotomy alone group (F)and fistulotomy with marsupialization group(FM). The primary outcome was the healing time secondary outcomes included postoperative pain, operating time, incontinence and recurrence. Results: Mean age of group (F) patients was 37.55 ± 1.96 years with a male: female ratio of 19:6 while the mean age of group (FM) patients was 36.30 ± 3.03 years with a male: female ratio of 21:4. Mean operative time in the group (F) was 23.5±3.3 minutes while in the group (FM) It was 29.00± 4.595 minutes difference is statistically significant. Mean time for complete healing in group (F) was 6.9 ±0.73 weeks while in group (FM) was 4.80 ±0.96 weeks difference is significant statistically. Mean postoperative pain score by visual analogue scale in the group (F) was 3.4 ± 1.2 while in the group (FM) it was 3.3 ± 1.3 this difference is statistically non-significant. No recurrences or incontinence. Conclusions: Study demonstrated faster-wound healing when adding marsupialization to fistulotomy compared to fistulotomy alone. There is an increase operative time with marsupialization. This effect is minimal when compared with the benefits of enhanced healing. Limitations are mainly the inadequate sample size and inadequate follow-up period.